Littoral Sediment From Rivers: Patterns, Rates and Processes of River Mouth Morphodynamics - Warrick, Jonathan A. (Frontiers in Earth Science, 2020)
Rivers provide important sediment inputs to many littoral cells, thereby replenishing sand and gravel of beaches around the world. However, there is limited information about the patterns and processes of littoral-grade sediment transfer from rivers into coastal systems. Here I address these information gaps by examining topographic and bathymetric data of river mouths and constructing sediment budgets to characterize time-dependent patterns of onshore, offshore, and alongshore transport. Two river deltas, which differ in their morphology, were used in this study: the Elwha River, Washington, which builds a mixed sediment Gilbert-style delta, and the Santa Clara River, California, which builds a cross-shore dispersed sand delta from hyperpycnal flows. During and after sediment discharge events, both systems exhibited a similar evolution composed of three phases: (i) submarine delta growth during offshore transport of river sediment, (ii) onshore-dominated transport from the submarine delta to a subaerial river mouth berm, and (iii) longshore-dominated transport away from the river mouth following subaerial berm development. Stage (ii) occurred within days to weeks for the systems studied and was associated with the greatest rates of net erosion and deposition. These morphodynamics were similar to simple equilibrium profile concepts that included an onshore-dominated cross-shore transport rule. Additionally, both study sites revealed that littoral-grade sediment was initially exported to depths beyond the active littoral cell (i.e., below the depth of closure) during the stage (i). Following several years of reworking by coastal processes, bathymetric surveys suggested that 14% and 46% of the original volume of littoral-grade sediment discharged by the Santa Clara and Elwha Rivers, respectively, continued to be below the depth of closure. This provides evidence that the full volume of littoral-grade sediment discharged by small rivers may not be integrated into littoral cells because of sand and gravel ‘losses’ to the continental shelf.